PENGARUH LAMA PEREBUSAN DALAM PEMBUATAN TEMPE BIJI NANGKA (Artocarpus heterophyllus) TERHADAP KUALITAS TEMPE SEBAGAI RANCANGAN LKS PADA KONSEP BIOTEKNOLOGI KONVENSIONAL KELAS XII SMA - Muliana gultom; Imam Mahadi; Mariani Natalina L (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract : Tempe is a food produced by a simple fermentation technique by Rhizopus oligosporus. During this tempe on the market only the soy-based. While the last few years soybean production in Indonesia continues to decrease and not able to meet the needs. Therefore, it is necessary to develop the manufacture of tempe that uses other raw materials whose nutritional value is not inferior to the tempe of soybean such as jackfruit seeds. The purpose of this research is to know the effect of the old boiling effect on the quality of Tempe seed of jackfruit (Artocarpus heterophyllus) tempe and the result of this research can be used for the development of LKS SMA of Conventional Biotechnology material. This research consists of 2 stages, namely the first stage, making tempe while the second stage of LKS development from the research. This research was done using experimental method with Completely Randomized Design (RAL) which consist of 5 treatments and 3 replications. The result of this research is concluded that in terms of content, protein content and fat content and organoleptic, K2 treatment is a good time in making tempe at Protein content while in the K4 treatment a good time in making tempe at fat content with 75 minutes boiling duration. The results of the research can be developed as LKS SMA Conventional Biotechnology material.Keywords: Tempe, jackfruit seed, conventional biotechnology, LKS.